Design of Distillation Equipment for Extracting Atsiri Oils from Serai Wangi Leaves Using the Steam and Water Method - Syafrizal, Muhammad; Irwansyah; Siswo Pranoto; Idris, Muhammad; Darianto, Darianto; Indra Hermawan (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2024)
Distillation is a technique for extracting Atsiri oils from various plants, one notable example being the Serai Wangi plant (Cymbopogon nardus), a type of herb commonly used in medicine, beauty products, and even as an additive to fuel. Atsiri oils from Serai Wangi can be produced through various methods, such as extraction. The advantage of this method is that it does not require high temperatures, thereby preventing the oil from degrading easily. Consequently, this distillation equipment design was developed to assist farming communities in acquiring an efficient distillation machine. The design process began with a literature study related to the design of distillation equipment. It involved calculating the design of the device and testing the functionality of the distillation equipment. The parameters observed were the effective capacity of the device, its performance, and the yield results. The outcome of this Serai Wangi oil distillation equipment design, featuring an evaporation tank, is that the evaporation process, where the burning furnace heats the water in the tank and steam is directed to the condenser through a connecting pipe, operates efficiently and can produce Atsiri oils of high quality and quantity.